2001
DOI: 10.1139/cjm-47-7-595
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium population dynamics in the pea rhizosphere of rhizobial inoculant strain applied in different formulations

Abstract: The effect of inoculant formulation on the population dynamics of rhizobia in the pea rhizosphere was investigated using a streptomycin-resistant mutant of Rhizobium leguminosarum bv. viceae NITRAGIN128C56G (128C56G strR). The isolate was formulated into liquid, peat powder, and granular peat carriers, and was tested on pea at field sites near Saskatoon, Saskatchewan, and Beaverlodge, Alberta, in 1996 and 1997. The liquid and peat powder formulations were applied to seed while the granular inoculant was applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Nodulation, seed yield and protein content of field pea showed that soil-applied granular inoculant was usually of greater benefit than seed-applied liquid inoculant. This is supported by earlier results on different parameters of soybean (Graham et al 1980) and field pea (Rice et al 2000;Hynes et al 2001). Granular inoculant was shown to be more effective than liquid inoculant in increasing nodule number and weight at low pH (4.4 to 5.4) but similar at pH 6.6 (Rice et al 2000).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Nodulation, seed yield and protein content of field pea showed that soil-applied granular inoculant was usually of greater benefit than seed-applied liquid inoculant. This is supported by earlier results on different parameters of soybean (Graham et al 1980) and field pea (Rice et al 2000;Hynes et al 2001). Granular inoculant was shown to be more effective than liquid inoculant in increasing nodule number and weight at low pH (4.4 to 5.4) but similar at pH 6.6 (Rice et al 2000).…”
Section: Discussionsupporting
confidence: 82%
“…Granular inoculant was shown to be more effective than liquid inoculant in increasing nodule number and weight at low pH (4.4 to 5.4) but similar at pH 6.6 (Rice et al 2000). Hynes et al (2001) suggested that rhizobia formulated as a liquid were more likely to suffer more from environmental stresses such as excess soil moisture than rhizobia in other formulations.…”
Section: Discussionmentioning
confidence: 97%
“…Desi chickpea grown on the clay produced 37% more root nodules and 75% greater nodule mass measured at flowering than when grown on the silt loam soil under comparable growing conditions. Hynes et al (2001) observed that colonization of the rhizosphere of dry pea was significantly reduced when soil moisture was low. Postma et al (1989) observed better survival of Rhizobium in fine-textured than in coarse-textured soils.…”
Section: Seed Yieldmentioning
confidence: 88%
“…In field experiments conducted in Alberta and Saskatchewan, the survival of R. leguminosarum bv. viciae on pea seed soon after inoculation and colonization of the rhizosphere of pea plants were clearly shown to be lower with liquid inoculant than with peat inoculant or granular inoculant under excessive soil moisture conditions (Hynes et al 2001).…”
Section: Nodulationmentioning
confidence: 93%